The impact of environmental, social and governance (ESG) scores on stock market: evidence from G7 countries - Kevser, Mustafa; Tunçel, Mert Baran; Gürsoy, Samet; Zeren, Feyyaz (Emerald Publishing, 2024)
Purpose: This study aims to examine the effect of environmental, social and corporate governance (ESG) scores on stock markets for the period from February 2018 to December 2022 for G7 countries. Even though ESG is an established area of investigation, prior research has paid inadequate attention to the nexus of ESG scores and stock markets in G7 (Germany, USA, UK, Italy, France, Japan and Canada) countries. Design/methodology/approach: This study covers G7 countries and uses a data set, which includes ESG scores and stock market returns from reporting channels including financial websites, and international indexes, between February 2018 and December 2022. Cross-section dependency and homogeneity tests were used with Konya (2006) panel causality test to investigate the relations of ESG scores and stock markets, and the research also conducted a separate analysis for each sub-dimension. Homogeneity/heterogeneity tests were also carried out in the research. Findings: The findings suggest that causality from ESG scores to stock market (DAX) was determined only for Germany. Accordingly, it is understood that German companies have started to implement corporate social responsibility and ESG practices in their management strategies and reporting. These findings offer important implications for those who are considering investing in G7 countries, whether or not to consider ESG scores. Originality/value: In this context, the research contributes to the existing literature on the relationships between ESG scores and stock markets, which are seen as a vital tool to meet the expectations of stakeholders. © 2023, Emerald Publishing Limited.
Keywords: Corporate social responsibility; ESG; G7 countries; Konya panel causality test; Stakeholder theory; Stock market